Bioutilization of the distillery stillage of different grain species from bioethanol production - Danilova, Katerina; Oliynichuk, Sergey; Verbytskyi , Sergey (Ecological Questions, 2023)
Wastewater from bioethanol plants is classified as highly concentrated in terms of organic pollution precisely due to distillery stillage. The main problem in the disposal of distillery stillage is the processing of the liquid phase, the volume of which is up to 92% of all wastewater from a bioethanol plant. The existing wastewater treatment technologies of a bioethanol plant can be conditionally divided into four types: evaporation, aerobic biological treatment with fodder yeast production, anaerobic stillage treatment with biogas production, combined schemes. The aim of our work was to study a combined method for cleaning grain stillage by the anaerobic-aerobic method with the immobilization of microorganisms on a fibrous carrier. Physicochemical parameters of grain stillage and purified methane mash were determined according to generally accepted methods for analyzing wastewater from distilleries. Under anaerobic conditions, biogas was formed from distillery stillage, including low molecular weight organic compounds – methane, carbon dioxide, organic acids. After the first anaerobic stage of treatment, the pollution of wastewater decreased by 8-10 times, after which it was fed to the aerobic stage of post-treatment, which was carried out by microorganisms immobilized on a fixed carrier, which reduced the removal of biomass with the flow of purified water and improved treatment performance. The chemical oxygen demand (COD) of methane mash after the 1st stage of anaerobic fermentation was 1360 mg/dm3 compared to the initial COD of grain stillage of 15800 mg/dm3, which ensured a purification efficiency of 91.4%. The purification efficiency according to biochemical oxygen demand in five days (BOD5) was 97.5%. After the aerobic stage, the purification efficiency was 98.2% in terms of COD and 99.8% in terms of BOD5. The values of the content of total phosphorus also decreased by almost 20 times, nitrogen – by 9 times, sulfates – by 5 times. The advantages of the proposed method of wastewater treatment of bioethanol plants over existing ones are the ability to treat wastewater with any concentration of pollutants and additional obtaining of fuel – biogas, which can be used to replace natural gas, solving the problem of removing the biomass of microorganisms from the purification zone due to their fixation on a fibrous fixed carrier.